Pediatric precision oncology: “better three hours too soon than a minute too late” - Marshall, Mark; Ivanovich, Jennifer; Schmitt, Morgan; Helvie, Amy; Langsford, Lisa; Casterline, Jennifer; Ferguson, Michael (Frontiers in Oncology, 2023)
Precision oncology is defined as the selection of an effective treatment for a cancer patient based upon genomic profiling of the patient’s tumor to identify targetable alterations. The application of precision oncology toward pediatric cancer patients has moved forward more slowly than with adults but is gaining momentum. Clinical and pharmaceutical advances developed over the past decade for adult cancer indications have begun to move into pediatric oncology, expanding treatment options for young high-risk and refractory patients. As a result, the FDA has approved 23 targeted drugs for pediatric cancer indications, moving targeted drugs into the standard of care. Our precision oncology program is in a medium sized children’s hospital, lacking internal sequencing capabilities and bioinformatics. We have developed methods, medical and business partnerships to provide state-of-the-art tumor characterization and targeted treatment options for our patients. We present here a streamlined and practical protocol designed to enable any oncologist to implement precision oncology options for their patients.